Molecular detection and characterization of Giardia spp., Cryptosporidium spp., and Blastocystis in captive wild animals rescued from central Colombia (2023)
Cryptosporidium, Giardia, and Blastocystis are significant causes of diarrhea worldwide. However, studies on their prevalence in wild animals are limited, compared to humans and domestic animals. In this study, we collected 23 stool samples from captive wild rescued animals in Boyacá, Colombia. Using conventional PCR, we detected Cryptosporidium spp., Giardia spp., and Blastocystis in over half of the samples (69.6%). Cryptosporidium spp. (43.5%) were the most commonly found, followed by Giardia spp. (39.1%) and Blastocystis (13.0%). Co-infections involving these parasites were also observed. Subsequent genotyping revealed Cryptosporidium canis and Cryptosporidium ryanae as the predominant species. These findings contribute valuable information about the ecoepidemiology of intestinal parasites in Colombian wild animals.